2014
DOI: 10.1159/000360414
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Self-Efficacy of Managing Behavior Problems for Family Caregivers of Vascular Dementia and Alzheimer's Disease Patients

Abstract: Background: Little is known about the differences in patients' behavioral problems and health outcomes of family caregivers of patients with vascular dementia (VaD) and Alzheimer's disease (AD). Methods: A secondary analysis of baseline data on a subsample of caregiver-dementia patient dyads in a randomized clinical trial. Results: Family caregivers of VaD patients reported higher self-efficacy than caregivers of AD patients in handling verbally nonaggressive and verbally aggressive behaviors. Caregivers of Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…The final model consisted of educational level, burden and mastery, representing the ‘background and contextual factors’, ‘secondary appraisal’ and ‘mediator’ domains in the stress-appraisal model (22). While the influence of caregiver burden and low education on caregivers’ outcomes is consistent with past studies (34, 36), our findings on the prognostic potential of mastery on caregivers’ risk of depression are novel. Notably, among the three components, mastery contributed the highest to the overall risk score.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The final model consisted of educational level, burden and mastery, representing the ‘background and contextual factors’, ‘secondary appraisal’ and ‘mediator’ domains in the stress-appraisal model (22). While the influence of caregiver burden and low education on caregivers’ outcomes is consistent with past studies (34, 36), our findings on the prognostic potential of mastery on caregivers’ risk of depression are novel. Notably, among the three components, mastery contributed the highest to the overall risk score.…”
Section: Discussionsupporting
confidence: 90%
“…Caregiver demographic risk factors included older age (≥65 years) (6), marital status (single) (5), relationship to care-recipient (spouse) (33, 34), working status (33) and sex (female) (34, 35). Social economic status indicators included low education (secondary school or lower) (34, 36) and housing type (public housing). Indicators of care demands such as living with care-recipient (33) and the absence of a domestic helper were also included.…”
Section: Methodsmentioning
confidence: 99%
“…Our research was targeted at exploring the influencing factors associated with HRQOL among family caregivers of patients with AD. Similar to other national studies, 6,18 the present study investigated the low scores of HRQOL in AD patientsʼ caregivers in China; the average HRQOL score was obviously lower than the general population, a relative part of caregivers were dissatisfied with their quality of life, and found that the level of burden, chronic diseases of caregivers, social support, and neuropsychiatric symptoms of patients were correlated with HRQOL.…”
Section: Discussionsupporting
confidence: 70%
“…However, they often neglect their own care, have been in a state of long-term depression, conceal their inner true feelings, ultimately resulting in affects to their physical and mental health. 6 Most studies conducted in Western populations showed three-quarters of family caregiversʼ social lives have been affected, with 60% of caregivers reported having psychological barriers; 70% of caregivers suffer from pessimism and nervousness, and a considerable number of people feel fatigue, depression and loneliness. 7,8 In recent years, academics have begun to pay attention to health-related quality of life (HRQOL) of caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…A lack of confidence about dealing with challenging behavioural needs has been reported to be associated with increased stress in family carers in dementia (e.g. Kuo, Huang, Hsu, & Yea-Ing, 2014). Further research is merited into the impact of the attributions observed in this study on the emotional response of family carers to challenging care needs and on their attempts to manage those needs.…”
Section: Discussionmentioning
confidence: 71%